13 Effects of bismuth subsalicylate and calcium-ammonium nitrate on in vitro fermentation of a high-concentrate substrate. (29th July 2019) - Mejia-Turcios, Sebastian E; Stotz, Miranda K; Osorio, Andrea M; Urso, Philip M; Jennings, Thomas G; Espinoza, Nadira; Kondratovich, Lucas; Carvalho, Luis F; Sandes, Michael D; Sarturi, Jhones O; DiLorenzo, Nicolas; Crossland, Whitney; et al.
Abstract: An experiment was performed to determine the effects of bismuth subsalicylate (BSS) and calcium-ammonium nitrate (CAN) on in vitro fermentation of a high-concentrate (87% concentrate, DM basis) substrate. Serum bottles containing 20 mL of a 2:1 buffer:ruminal fluid inoculum and 0.2 g of substrate were incubated for 24 h. Four ruminally cannulated steers (BW = 520 ± 30 kg) were used as ruminal fluid donors and each donor was considered a block. Treatments were arranged in a 2 × 2 factorial with the following factors: BSS (0 or 0.33%, DM basis) and CAN (0 or 2.22%, DM basis). Treatments were made isonitrogenous with urea. In vitro organic matter digestibility (IVOMD) was determined in separate 100-mL centrifuge tubes. Data were analyzed using the MIXED procedure of SAS with the fixed effect of BSS, CAN, BSS × CAN, and the random effect of donor. An interaction (P < 0.01) was observed for total gas production (TGP). When CAN was included, without BSS, TGP was increased (P < 0.01); however, the combination of CAN with BSS did not affect (P = 0.85) TGP when compared to the combination of urea and BSS. Ammonia-N tended (P = 0.10) to increase when CAN was used as N source rather than urea. In vitro OM digestibility (P > 0.23) and final pH (P > 0.66) of in vitro ruminal fermentation were not affected by treatments. A tendency (P = 0.06) for an interaction regarding the production of H2 S was observed; however, there were no treatment mean differences (P > 0.28). The combination of CAN and BSS did not negatively affect in vitro fermentation parameters such as OM digestion and gas production; however, a reduction in H2 S with the combination of BSS and CAN may indicate potential benefits of such feeding strategies for feedlot cattle